Borges to Put Together 101 Years of his Birth (Ultraism: an Unknown Part of his Lyrical Production) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
The work of Jorge Luis Borges is an endless puzzle whose number of pieces seems inexhaustible. Although Borges has achieved international recognition thanks to the erudition, rigor, and philosophical and metaphysical background of his short fiction and his essay production, poetry has also equaled the mastery of his prose (note)